Wise Governance – Elements of the digital strategies of municipalities - Christian SCHACHTNER (Smart Cities and Regional Development Journal)
The innovation fields of municipalities are based on the creation of added value for the local population by creating a portfolio of digital implementation projects as a "proof of concept".